Enhancing excel business tools with additional relational and recursive capabilities - Ramos, P. (2019)
This paper presents a new plug in that enriches spreadsheet capabilities mainly in what concerns its potential regarding relational queries and recursive computational processes. Currently some apparently trivial and useful queries can only be handled with the support of programming skills. Spreadsheet users with low computer science skills should have a natural and easy way to handle those queries within the spreadsheet, without relying on external programming (e.g., VBA). The tool we have developed can be used with Prolog technology, and provides those features to the most used professional spreadsheet: Microsoft Excel. Throughout the paper we explore the plug-in features with several business examples.